THE DISCOURSE OF POLYGAMY IN THE FILM BERBAGI SUAMI (LOVE FOR SHARE) 2006 - Ni Made Widisanti Swetasurya (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
Polygamy in the context of  Indonesian society is frequently seen as an issue that is related to  pro and contra attitudes shown by women in terms of how they respond to such marriage system. The issue of polygamy raised in this article is focusing on the discourse of polygamy built in this film, Berbagi Suami (Love for Share) (2006), through the study of the female central characters that experienced polygamous marriages. The aim is to reveal the discourse of polygamy in this film through Hall's constructionist approach and Foucault's discourse concept using descriptive analysis methods and semiology. The results of the analysis show that the discourse of polygamy in the Indonesian context is described as a matter of pros and cons that comes from women’s responses to polygamous marriages. Despite the pros and cons, polygamous marriage is still seen as a complex marriage system that is detrimental to women.  Women are represented as victims that are shown by the impacts obtained from polygamous marriages such as economic hardship, not getting the justice they deserve, physical abuse, exhausting physiological and physiological conditions, and social labeling.